Pertumbuhan Ekonomi dan Kemiskinan Provinsi Bengkulu : Studi Komparatif Sebelum dan Selama Pandemi Covid-19 - Ega Permana Tanjung; Yuhendri L V (Universitas Negeri Padang, 2023)
This research goals to analyze differences in poverty rates and economic growth rates in Bengkulu province before and during the Covid-19 pandemic. This research uses a quantitative approach with a comparative study type. The data analysis technique used is paired sample t-test and is sourced from secondary data. The result show no significant difference the poverty rate with economic growth rate of regencies and cities in Bengkulu Province before and during the Covid-19.